Exploration of Network Information Security Technology and Prevention in the Digital Age - Hongfei Xiao (Forest Chemicals Review)
Since the digital age, the virtual and open nature of network information technology has led to frequent information security problems, such as hidden dangers of information leakage, risk of cyber attacks, insufficient audit supervision, backward security technology, etc. Therefore, how to protect users’ information while developing information technology has become a big problem. In this paper, in order to protect the data security and privacy in the digital age, the problems existing in the current application of information technology were analyzed, and the solutions to the information security problems were put forward, such as strengthening the prevention of network information security technology by putting an end to the hidden dangers of information leakage, preventing the risk of network attacks, strengthening audit supervision, and cultivating security technical talents.